Resistively Loaded Dipole Characteristics - Hajach, Peter; Hartansky, Rene (Radioengineering Society, 2003)
Resistively loaded dipole is very often used to measuring the electromagnetic field in EMC testing. The dipole is a traveling wave antenna, where its resonance is eliminated. The paper includes the computation of the current distribution and radiation pattern of this dipole. The characteristics were obtained by moment method, Hallen method and Wu-King method. The unique modification of presented methods has been made. The comparison of used methods has been presented in paper conclusions.
Keywords: Antenna; electromagnetic field; electromagnetic com-patibility; analytical and numerical methods of anten-na analysis